Number 2: Chronic Obstructive Pulmonary Disease: The Importance of Exercise - Norman L Jones (Canadian Respiratory Journal)
Patients with chronic obstructive pulmonary disease (COPD - chronic bronchitis, emphysema, asthma) are often limited in their capacity to exercise, mainly because they experience shortness of breath or muscle fatigue. The reasons for shortness of breath are dealt with in another patient page (Can Respir J 2000;7(1):35-36), and include narrowing of the airways, poor lung function leading to falls in the amount of oxygen carried in the blood and weak muscles for breathing. Easy fatiguability may be because of muscle weakness or changes in muscle function, related to inactivity and ageing. Other less common factors include heart problems associated with COPD, and other coexisting health problems, such as anemia and arthritis.